Investigating English Students’ Strategies for Improving Oral Fluency and Self-Confidence at English Study Program Sriwijaya University - Septiany, Nurbaiti; Zuraida, Zuraida (Universitas Nurul Jadid, 2025)
This study intended to find out the strategies used by English students to improve their oral fluency in English and how these strategies that contribute to building students’ self-confidence. This study used a qualitative approach with the method of data collection through semi-structured interview to explore students' experiences. The participants in this study were 2nd semester students of English Department of Sriwijaya University Palembang, consist of 14 students of Class A Palembang and 14 students of Class B Palembang. The data in this study was collected through an interview with 10 main questions. The results of the study show that the strategies used by the students to improve their oral fluency include watching videos or movies in English, as well as learning and practicing with friends. These strategies not only help improve oral fluency, but also reduce anxiety and increase students' self-confidence in communication using English. This study contributes to the development of literature on strategies to improve oral fluency and self-confidence in English language learning, and provides insights for educators on how to support students through relevant and experiential methods.